1993
DOI: 10.1080/09670269300650381
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of the diatoms (Bacillariophyta). I. Origin of the group and assessment of the monophyly of its major divisions

Abstract: The diatoms are one of the best characterised algal groups. Despite this, little is known of the evolution of the group from the earliest cell to the myriad of taxa known today. Relationships among taxa at the family or generic level have been recognised in some diatoms. However, relationships at higher taxonomic levels are poorly understood and have often been strongly influenced by the first appearances of key taxa in the fossil record. An independent assessment of relationships among the diatoms at these hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
66
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(67 citation statements)
references
References 50 publications
1
66
0
Order By: Relevance
“…Simonsen 1979) that the pennate diatoms evolved from the centric forms because they appear later in the geological record (which had been noted also by Fritsch 1935, p. 642), is supported unambiguously by molecular phylogenies (see below, this section). Likewise, Simonsen's view that centric diatoms are paraphyletic (though he did not use this terminology) is also clearly demonstrated by molecular data, which were presented first by Medlin et al (1993). However, molecular analyses have also brought several surprises.…”
Section: The Impact Of Molecular Data On Diatom Systematicsmentioning
confidence: 99%
See 4 more Smart Citations
“…Simonsen 1979) that the pennate diatoms evolved from the centric forms because they appear later in the geological record (which had been noted also by Fritsch 1935, p. 642), is supported unambiguously by molecular phylogenies (see below, this section). Likewise, Simonsen's view that centric diatoms are paraphyletic (though he did not use this terminology) is also clearly demonstrated by molecular data, which were presented first by Medlin et al (1993). However, molecular analyses have also brought several surprises.…”
Section: The Impact Of Molecular Data On Diatom Systematicsmentioning
confidence: 99%
“…The Lithodesmiales possess a central rimoportula, although this has a characteristic bilabiate internal morphology, which one easily can envisage having been formed by the closure of a single open tube. This fact led Medlin et al (1993) and Medlin & Kaczmarska (2004) to suggest that the central strutted process could be homologous with the bilabiate process of the Lithodesmiales. Kaczmarska et al (2006) have suggested further that the external tubes of the marginal strutted processes could be formed by a fragmentation, then encircling and fusing of the marginal fringe in the Lithodesmiales to form hollow tubes above the pore structure of the fultoportula.…”
Section: The Thalassiosiralesmentioning
confidence: 99%
See 3 more Smart Citations